Line-Field Confocal Optical Coherence Tomography: A New Skin Imaging Technique Reproducing a “Virtual Biopsy” with Evolving Clinical Applications in Dermatology - Cappilli, Simone; Paradisi, Andrea; Di Stefani, Alessandro; Palmisano, Gerardo; Pellegrino, Luca; D’Onghia, Martina; Ricci, Costantino; Tognetti, Linda; Verzì, Anna Elisa; Rubegni, Pietro; Del Marmol, Veronique; Lacarrubba, Francesco; et al. (Diagnostics (Basel), 2024)
Background: Line-field confocal optical coherence tomography is a novel technology able to reproduce a “virtual biopsy” of the skin. The aim of this review is to explore the application of line-field confocal optical coherence tomography (LC-OCT) in various skin diseases, covering skin cancers, inflammatory and infectious skin diseases, genetic diseases, cosmetic procedures, and less common disorders. Methods: Study selection was conducted based on LC-OCT and using pertinent MeSh terms, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines from inception to March 2024; to evaluate the quality and risk of bias of studies, Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) was used. Results: the search retrieved 154 papers according to the selection criteria; after removing publications by one or more of the exclusion criteria, a total of 96 studies were found to be suitable for the analysis. Conclusions: Increasing evidence supports the use of LC-OCT as an adjunctive diagnostic tool for the in vivo diagnosis of a variety of skin tumors. As this device can be considered a “bridge” between dermoscopy and histopathology, widening applications in numerous fields of clinical dermatology, including inflammatory skin disease treatment, presurgical mapping, cosmetic procedures, and monitoring of non-invasive therapies, have been explored.